Human and Monkey Striatal Interneurons Are Derived from the Medial Ganglionic Eminence But Not from the Adult Subventricular Zone - Wang, Congmin (J Neurosci, 2014)
In adult rodent and monkey brains, newly born neurons in the subventricular zone (SVZ) in the wall of the lateral ventricle migrate into the olfactory bulb (OB) via the rostral migratory stream (RMS). A recent study reported that interneurons are constantly generating in the adult human striatum from the SVZ. In contrast, by taking advantage of the continuous expression of Sp8 from the neuroblast stage through differentiation into mature interneurons, we found that the adult human SVZ does not generate new interneurons for the striatum. In the adult human SVZ and RMS, very few neuroblasts were observed, and most of them expressed the transcription factor Sp8. Neuroblasts in the adult rhesus monkey SVZ–RMS–OB pathway also expressed Sp8. In addition, we observed that Sp8 was expressed by most adult human and monkey OB interneurons. However, very few Sp8+ cells were in the adult human striatum. This suggests that neuroblasts in the adult human SVZ and RMS are likely destined for the OB, but not for the striatum. BrdU-labeling results also revealed few if any newly born neurons in the adult rhesus monkey striatum. Finally, on the basis of transcription factor expression, we provide strong evidence that the vast majority of interneurons in the human and monkey striatum are generated from the medial ganglionic eminence during embryonic developmental stages, as they are in rodents. We conclude that, although a small number of neuroblasts exist in the adult human SVZ, they do not migrate into the striatum and become mature striatal interneurons.